“Fake it till You Make it”! Contaminating Rubber Hands (“Multisensory Stimulation Therapy”) to Treat Obsessive-Compulsive Disorder - Jalal, Baland; McNally, Richard J.; Elias, Jason A.; Potluri, Sriramya; Ramachandran, Vilayanur S. (Frontiers in Human Neuroscience, 2020)
Obsessive-compulsive disorder (OCD) is a deeply enigmatic psychiatric condition associated with immense suffering worldwide. Efficacious therapies for OCD, like exposure and response prevention (ERP) are sometimes poorly tolerated by patients. As many as 25 percent of patients refuse to initiate ERP mainly because they are too anxious to follow exposure procedures. Accordingly, we proposed a simple and tolerable (immersive yet indirect) low-cost technique for treating OCD that we call “multisensory stimulation therapy.” This method involves contaminating a rubber hand during the so-called “rubber hand illusion” (RHI) in which tactile sensations may be perceived as arising from a fake hand. Notably, Jalal and Ramachandran (2015), showed that such fake hand contamination during the RHI provokes powerful disgust reactions in healthy volunteers. In the current study, we explored the therapeutic potential of this novel approach. OCD patients (n = 29) watched as their hidden real hand was being stroked together with a visible fake hand; either synchronously (inducing the RHI) (i.e., the experimental condition; n = 16) or asynchronously (i.e., the control condition; n = 13). After 5 minutes of tactile stimulation, the rubber hand was contaminated with fake feces, simulating conventional exposure therapy. Intriguingly, results suggested sensory assimilation of contamination sensations into the body image via the RHI: patients undergoing synchronous stimulation did not report greater contamination sensations when the fake hand was initially contaminated relative to asynchronous stroking. But contrary to expectations, they did so after the rubber hand had been contaminated for 5 minutes; as assessed via disgust facial expressions (a secondary outcome) and in vivo exposure (upon discontinuing the illusion). Further to our surprise, synchronous and asynchronous stroking induced an equally vivid and fast emerging illusion, which helps explain why both conditions initially (5 minutes after initiating tactile stimulation) provoked contamination reactions of equal magnitude. This study is the first to suggest heightened malleability of body image in OCD. Importantly, it may pave the way for a tolerable technique for the treatment of OCD—highly suitable for poorly resourced and emergency settings, including low-income and developing countries with minimal access to high-tech solutions like virtual reality.